ANALISIS EFEKTIFITAS PROSES PENGOLAHAN LIMBAH PT. INDONESIA POWER UNIT BISNIS PEMBANGKITAN (UBP) BALI BERBASIS MICROSOFT VISUAL FOXPRO - N. NGR. ADISANJAYA; I Wayan Budiarsa Suyasa; I Ketut Sundra (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2011)
Indonesia Power Generating Business Unit Bali is a state-owned enterprises (SOE.5) engaged in the electrification of Java and Bali. This company manages 15 units of power plants, 11 diesel and 4 PLTG which total 201.29 MW of power generated. The amount of power it will produce a greater flow of waste so that waste processing technology needed a good and effective. This study aims to determine the quality of waste water pollutant levels and the effectiveness of waste processing, that data analysis and processing using Microsoft Visual FoxPro programming language. Sampling was conducted in February and March of 2011 with the parameters of temperature, pH, dissolved solids (TDS), oil and grease, BODs, COD, sulfide (H2S), cadmium (Cd), lead (Pb) and dissolved iron (Fe). This study is descriptive with a primary method of data collection with laboratory tests. The study was conducted by comparing the quality of waste water in TS I, which on the inlet separator I, TS II; namely the outlet separator II and TS III, namely the outlet waste treatment process as a whole with the specified quality standards. The results are less optimal effectiveness of wastewater treatment poses on cadmium (Cd) by the average value of 61.32% because it is below the prevailing standards of effectiveness by the average value of 97.17% so that its effluent quality with average of 0.14 ppm exceeds the standard set that is equal to 0.01 ppm. This is due to the absence of alternative waste treatment processes to reduce the content of heavy metals, especially cadmium (Cd) and to improve the effectiveness of the previous